Host Defense Skin Peptides Vary with Color Pattern in the Highly Polymorphic Red-Eyed Treefrog - Davis, Leyla R.; Klonoski, Karina; Rutschow, Heidi L.; Van Wijk, Klaas J.; Sun, Qi; Haribal, Meena M.; Saporito, Ralph A.; Vega, Andres; Rosenblum, Erica B.; Zamudio, Kelly R.; Robertson, Jeanne M. (Frontiers in Ecology and Evolution, 2016)
Patterns of phenotypic variation across a geographic range provide important insights into evolutionary processes underlying diversification and speciation. Most evolutionary studies use putatively neutral markers to examine evolutionary diversification. However, functional phenotypes such as gene-encoded host-defense polypeptides (HDPs) could provide key insights into the processes of population differentiation, yet they are rarely included in population analyses. The red-eyed treefrog, Agalychnis callidryas (Cope, 1862), exhibits regional variation in multiple traits, including color pattern and body size across a narrow geographic range. This treefrog produces bioactive peptides exuded onto the skin surface, presumably for pathogen and predator defense. However, the geographic patterns of variation in peptides and the factors that mediate intraspecific peptide variation across the range of this species remain untested. Here, we examine the roles of phylogenetic history, geographic barriers, geographic distance, and color-pattern variation as determinants of skin peptide diversity in 54 individuals among 11 populations across Costa Rica and Panama. Each of the five distinct Agalychnis color morphs are represented in our sample. We performed peptide mass fingerprinting and compared mass spectral data from skin peptide secretions to quantify divergence in peptide profiles among individuals, both within and among regions. We used two metrics to estimate genetic variation: genetic distance estimated from microsatellites and patristic distance estimated from mtDNA haplotype diversity. Matrix correspondence tests revealed that skin peptide variation is best predicted by differences in leg color pattern across all regions. In addition, we found that flank color pattern and phylogeny also explain differences in peptide diversity. Patterns of peptide differentiation and phylogenetic topology were incongruent in two regions, indicating a possible role of localized selection on peptide variation. Skin peptide profiles are useful in population differentiation studies of a polymorphic species as well as studies of selection and phenotype covariation among closely related species. Our results highlight the use of skin peptides as characters for future studies of population differentiation and contribute to our understanding of biogeography in Central America.